METHODS OF DIAGNOSING DEFORMATIONS OF BUILDING STRUCTURES - Terentyev, Olexander; Gorbatyuk, Ievgenii; Tyslenko, Oleksandr; Bykov, Vadym (SWorld-Ger Conference proceedings, 2024)
Modern information systems are a new type of integrated information systems, which on the one hand include data processing methods of many existing automated systems, on the other hand, have specificity in the organization and processing of data. In pract